2014
DOI: 10.1681/asn.2012101014
|View full text |Cite
|
Sign up to set email alerts
|

CD73-Dependent Generation of Adenosine and Endothelial Adora2b Signaling Attenuate Diabetic Nephropathy

Abstract: Nucleotide phosphohydrolysis by the ecto-59-nucleotidase (CD73) is the main source for extracellular generation of adenosine. Extracellular adenosine subsequently signals through four distinct adenosine A receptors (Adora1, Adora2a, Adora2b, or Adora3). Here, we hypothesized a functional role for CD73-dependent generation and concomitant signaling of extracellular adenosine during diabetic nephropathy. CD73 transcript and protein levels were elevated in the kidneys of diabetic mice. Genetic deletion of CD73 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 84 publications
1
30
0
Order By: Relevance
“…137 Production of adenosine, via CD73, is protective against diabetic nephropathy; 138 indeed, mice lacking CD73 exhibit a more severe form of renal dysfunction following induction of diabetes mellitus than wild-type littermates. 138 This study also found a selective induction of A 2B adenosine receptors in the vasculature, and use of mice with global or tissue-specific knockout of the A 2B adenosine receptor revealed that the protective role exerted by CD73-derived adenosine was mediated by endothelial A 2B adenosine receptor signalling. 138 The discrepancies regarding the harmful versus protective roles of A 2B adenosine receptors in the various studies are probably due to the different experimental approaches, such as the use of A 2B adenosine receptor knockout mice compared with p harmacological blockade of A 2B a denosine receptors in rats.…”
Section: Diabetic Nephropathysupporting
confidence: 57%
“…137 Production of adenosine, via CD73, is protective against diabetic nephropathy; 138 indeed, mice lacking CD73 exhibit a more severe form of renal dysfunction following induction of diabetes mellitus than wild-type littermates. 138 This study also found a selective induction of A 2B adenosine receptors in the vasculature, and use of mice with global or tissue-specific knockout of the A 2B adenosine receptor revealed that the protective role exerted by CD73-derived adenosine was mediated by endothelial A 2B adenosine receptor signalling. 138 The discrepancies regarding the harmful versus protective roles of A 2B adenosine receptors in the various studies are probably due to the different experimental approaches, such as the use of A 2B adenosine receptor knockout mice compared with p harmacological blockade of A 2B a denosine receptors in rats.…”
Section: Diabetic Nephropathysupporting
confidence: 57%
“…39 More recently, the genetic deletions of the adenosine A 2B receptor and of CD73 (a key enzyme that produces extracellular adenosine) in mice have been found to be associated with more severe diabetic nephropathy. 40 Increased eATP signaling via P2X 4 R due to hyperglycemia induces activation of the NLRP3 inflammasome, thus stimulating IL-1b and IL-18 release, with development of tubulointerstitial inflammation 41,42 (Table 2). Two studies revealed that in individuals with type 2 diabetes and diabetic nephropathy, P2X 4 R, P2X 7 R, and NLPR3 are upregulated compared with controls, and that tubular P2X 4 R expression colocalized in confocal analysis with NLRP3, IL-1b, and IL-18 expression.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…73 CD73 expression and adenosine are also elevated in diabetic mice. 74 Expression and activity of the equilibrative nucleoside transporters ENT-1 and -2 are reduced in diabetic rats, 75 indicating a tendency for extracellular adenosine accumulation in hyperglycemia. Concurrently, hyperglycemia upregulates expression of hypoxia-inducible factor1a, 76 which in turn upregulates expression of A 2B R 77 on mesangial cells and podocytes.…”
Section: A 2b R Signaling Promotes Renal Fibrosismentioning
confidence: 99%
“…However, it has been reported recently that the absence of endothelial A 2B R is associated with increased vascular endothelial growth factor levels and more severe diabetic nephropathy in a model of streptozotocin-induced diabetes. 74 This highlights the complexity in understanding the variable effects of different cells that express the A 2B R in diabetes. Of interest, Tak et al 74 further demonstrated that infusion of BAY 60-6583 (previously recognized as an agonist of the A 2B R) in a mouse model of streptozotocin-induced diabetes and in genetically diabetic Akita (Ins2 þ / À ) mice reduced the development of diabetic nephropathy.…”
Section: A 2b R Signaling Promotes Renal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation